Heavy mineral record from the east China sea inner shelf: Implications for provenance and climate changes over the past 1500 years. (1st September 2021) - Zhang, Kaidi; Li, Anchun; Liu, Xiting; Chen, Min-Te; Lu, Jian; Zhang, Jin; Wang, Hongli
Abstract: The heavy mineral composition and sensitive grain size changes from core SS4 retrieved from the mud wedge on the East China Sea inner shelf have been studied for better understanding provenance variations in the sediment and climate changes during the last 1500 yr. High dolomite content and occurrence of ubiquitous polysynthetic mica indicate that the sediments in core SS4 were mainly derived from the Yangtze River, while the relatively high epidote content represent the contribution of small local rivers from Zhejiang and Fujian provinces. The substantial decrease in the epidote/hornblende ratio since 730 yr BP manifests a decline in the relative contribution of sediment from the small local rivers to the core. We propose that the changes in drought/flood conditions in response to the East Asian winter monsoon (EAWM) and human activities might have been mainly responsible for changes in sedimentary characteristics. During 1400–730 yr BP, the core sediments were characterized by relatively finer sensitive grain size and high epidote/hornblende ratio, due to a possibly weaker EAWM (i.e., less Yangtze River-derived sediment transported by the southward coast current). This time interval coincides with the Sui-Tang Warm Period (1400–1130 yr BP) in China and the Medieval Warm Period (1000–730 yr BP) on a broader regional scale. The prolonged warm periods were, however, interrupted by three short cold phases at 1350–1280 yr BP, 1130–1000 yr BP and 870–750 yr BP, characterized by coarse sensitive grain size and decreased epidote/hornblende ratio. Between 360 and 150 yr BP, the sensitive grain size significantly coarsened, which corresponded to the Little Ice Age. Our new findings suggest that sedimentation processes of mud wedge formation are responsive to natural environmental change and human activity. Highlights: ∙ Provenance and climate changes have been detected in the East China Sea ∙Significant changes in the ratio of epidote/hornblende indicate source variations ∙The contribution of small local rivers has declined since 730 yr BP ∙Climate-driven drought/flood conditions and human activities are the main causes ∙The alternation of the warm and cold period is well recorded by heavy minerals